2014
DOI: 10.1016/b978-0-12-801105-8.00010-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in the Addicted Brain

Abstract: Addiction is due to changes in the structure and function of the brain, including neuronal networks and the cells that comprise them. Within cells, gene expression changes can track and help explain their altered function. Transcriptional changes induced by addictive agents are dynamic and divergent and range from signal pathway-specific perturbations to widespread molecular and cellular dysregulation that can be measured by “omic” methods and that can be used to identify new pathways. The molecular effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…The ultimate goal of genomic discovery-based approaches is to identify and characterize the biological function of gene networks that are causal to the disorder rather than individual gene functions (Mamdani et al, 2015; Ponomarev et al, 2012; Repunte-Canonigo et al, 2015; Zhou et al, 2014). In support of this hypothesis a recent study found that functional brain networks measured with resting-state fMRI are directly linked to correlated gene expression in post mortem human brain, suggesting that the emergent properties of gene networks endow function to neurocircuits (Richiardi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of genomic discovery-based approaches is to identify and characterize the biological function of gene networks that are causal to the disorder rather than individual gene functions (Mamdani et al, 2015; Ponomarev et al, 2012; Repunte-Canonigo et al, 2015; Zhou et al, 2014). In support of this hypothesis a recent study found that functional brain networks measured with resting-state fMRI are directly linked to correlated gene expression in post mortem human brain, suggesting that the emergent properties of gene networks endow function to neurocircuits (Richiardi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, addiction is thought to result from changes in brain structure and function (Zhou, Enoch, & Goldman, 2014). As summarized in twin/family study results, additive genetic influences, alone, are not expected to contribute to SUD.…”
Section: Non-additive Genetic Mechanisms Involved In Sudmentioning
confidence: 99%
“…These influences include: (1) methylation of specific genes, which generally reduce gene expression; (2) changes in microRNA production (miRNA), which are a class of small, noncoding regulatory RNAs that are central to regulating protein translation; and (3) histone modification via acetylation, which changes DNA conformation, altering accessibility for translation (Kenny, 2014; Zhou, et al, 2014). …”
Section: Non-additive Genetic Mechanisms Involved In Sudmentioning
confidence: 99%
“…In 2013, however, this number rose to over 17,000, a striking 45 new publications every day, in addition to increases in scientific meetings and grant directives dedicated to the subject. Today, epigenetic concepts have spread into fields that do not routinely address genetics (at least explicitly), such as ecology (Bossdorf et al 2008;Zucchi et al 2013;Burris and Baccarelli 2014), physiology (Ho and Burggren 2010), and psychology (Ngun and Vilain 2014;Zhou et al 2014). Despite its apparent popularity, the unfortunate fact is that the increased use of the term epigenetics is likely due more to inconsistencies in its definition than to a consensus of interest among scientists or a paradigm shift in the rules of inheritance.…”
mentioning
confidence: 99%